The Design and Development of an Attendance and Practical Exam Scoring System Using QR Code Based on IoT in the Laboratory of SMK TI ZAMIGA - Utami, Tria Fitri; Putra , Okta Andrica; Afira, Riandana (TOFEDU: The Future of Education Journal, 2025)
The development of information and communication technology has brought significant impacts in various sectors, including education, with the implementation of a more efficient attendance system. This research aims to develop a QR Code-based attendance system integrated with Internet of Things (IoT) technology at SMK TI ZAMIGA, considering that the manual attendance process that is still used today results in recording errors of around 20%. The designed system utilizes devices such as Arduino Mega, QR Code Scanner, Ultrasonic Sensor, and NodeMCU to record student attendance automatically and in real-time. In addition, this system allows teachers to input student practicum grades, with easy data access through a website built using PHP and XAMPP technology. With the development of this attendance system, it is expected to improve efficiency, security, and student discipline in the learning process.